The Prosperity Gospel and the Spirit of Consumerism According to Joel Osteen - Mundey, Peter (Pneuma, 2017)
This article explores the link between Protestantism and the spirit of consumerist capitalism by focusing on the prosperity gospel and one of its most prominent contemporary proponents—pastor, televangelist, and New York Times bestselling author Joel Osteen. Through in-depth content analysis of eight of Osteen’s most influential and widely read books, I explore the underlying assumptions of his teachings about faith, prosperity, and consumption. The broader implications of Osteen’s theology of money and consumption for American religion—especially the link between Protestant Christianity, consumerism, and the American Dream—are considered. Findings reveal Osteen’s support for the consumerist belief that happiness and ultimate meaning in life are linked with ever-increasing discretionary consumption. Godliness and nonessential consumption go hand in hand for Osteen, whose Christianized version of the American Dream and prosperity gospel teachings are important components of the spirit of twenty-first-century consumerist capitalism.